Discovery of indole analogues from Periplaneta americana extract and their activities on cell proliferation and recovery of ulcerative colitis in mice - Xie, Yuchen; Liang, Siwei; Zhang, Yifan; Wu, Taoqing; Shen, Yongmei; Yao, Shun; Li, Jing (Frontiers in Pharmacology, 2023)
As an important medicinal insect, Periplaneta americana (PA) has been applied for the treatment of wounds, burns, and ulcers with fewer side effects and a reduced recurrence rate, which provides great potential for developing new drugs based on its active constituents.The main chromatographic peaks determined by high performance liquid chromatography (HPLC) in the PA concentrated ethanol-extract liquid (PACEL) were separated, purified, and identified by semi-preparative LC, mass spectrum, and 1 H NMR spectroscopic analysis. The biological activities of the identified compounds were investigated by methylthiazolyldiphenyl-tetrazolium bromide (MTT) method based on in vitro human skin fibroblasts (HSF) and in vivo experiments based on dextran sulfate sodium (DSS)-induced ulcerative colitis (UC) mouse model. Furthermore, RT-qPCR of six genes related to inflammation or intestinal epithelial cell proliferation was employed to investigate the molecular mechanism of the indole analogues recovering UC in mice.Results: Five indole analogues were purified and identified from PACEL, including tryptophan (Trp), tryptamine (pa01), 1,2,3,4-tetrahydrogen-β-carboline-3-carboxylic acid (pa02), (1S, 3S)-1-methyl-1,2,3,4-tetrahydrogen-β-carboline-3-carboxylic acid (pa03) and (1R, 3S)-1-methyl-1,2,3,4-tetrahydrogen-β-carboline-3-carboxylic acid (pa04), among which the pa02 and pa04 were reported in PA for the first time. In vitro and in vivo experiments showed that PACEL, Trp, and pa02 had promoting HSF proliferation activity and intragastric administration of them could alleviate symptoms of weight loss and colon length shortening in the UC mice.Although recovery activity of the compound pa01 on the colon length was not as obvious as other compounds, it showed anti-inflammatory activity in histological analysis. In addition, The RT-qPCR results indicated that the three indole analogues could alleviate DSS-induced intestinal inflammation in mice by inhibiting pro-inflammatory cytokines (MMP7, IL1α) and down-regulating BMP8B expression.This study reported the isolation, purification, structure identification, and biological activity of the active indole analogues in PACEL. It was found for the first time that the PA extract contained many indole analogues and Trp, which exhibited good proliferation activity on HSF fibroblasts as well as anti-UC activity in mice. These indole analogues probably are important components related to the pharmacological activity in PA.